IMPACT OF WHOLE-BODY ELECTROMYOSTIMULATION AND RESISTANCE TRAINING ON BONE MINERAL DENSITY IN WOMEN AT RISK OF OSTEOPOROSIS - Pavlína Vaculíková; Adéla Paclíková; Michaela Kotková; Ivan Struhár; Dominika Nancy Balousová (The Sky)
In recent years, there has been an increasing interest in physical activity programs for older adults. Questions have been raised about the efficacy of programs regarding real effects on life. The purpose of the study is to compare the impact of ten weeks of Whole-Body Electromyostimulation (WB-EMS) and resistance training (RT) programs on one mineral density (BMD) and T-score values in women at risk of osteoporosis. The WB-EMS was carried out once per week (total: ten sessions), the RT was carried out twice per week (total: 20 sessions). Twenty-eight elderly women participated in the study, nine in a WB-EMS group (weight: 69.84±10.29kg; BMI: 25.04±4.18 kg/m2), eight in a RT group (weight: 74.16±4.19kg; BMI: 27.35±2.76 kg/m2), and ten in a control group (CG) (weight: 79.72±15.61kg kg; BMI 28.58±5.70 kg/m2). A dual-energy X-ray absorptiometry scanner (DXA) was used to assess body composition, BMD, and T-score values.  To identify the statistical significance of the differences between pre-test and post-test in all groups, the parametric t-test was used. Statistical significance was set at p ≤ 0.05. Although no significant differences were found in either BMD or T-score values, the study appeared to elicit some positive behaviour that could have an impact for more than ten weeks. The present study was designed to determine the effect of RT and WB-EMS on selected parameters in groups of women at risk of osteoporosis. Even though the results were not statistically significant, we consider the impact of programs on the level of BMD and T-score beneficial. Results show that the RT method is more practical. More tested subjects of the RT reported the same or higher level of BMD in the post-test compared to the WB-EMS method (RT 50% vs WB-EMS 44.7%). It was impossible to further investigate the significant relationships between selected parameters and intervention because the sample size was too small. Therefore, a further study with more focus on the duration of intervention and an increase in sample size is suggested.